Good Agricultural Practices as a Clean Production Alternative in the Citrus and Mango Production Process in the Municipality of Viotá (Cundinamarca, Colombia) - Gómez Orejuela, Ivonne Aillen; Vianchá Sánchez, Zulma Hasbleidy (Ingeniería Solidaria, 2017)
Introduction: This article is the result of the project “Characterization of the supply and distribution chain of mango and citrus production in the municipality of Viotá”, Cundinamarca, conducted in the framework of the Colciencias call for young researchers and innovators, in partnership with sena 2015. Such call seeks to strengthen the vocation for science, technology and innovation in young students of technical high school, technicians, technologists and university students, by creating learning opportunities. The project was carried out by students of the Industrial Engineering program at the Fundación Universitaria Agraria de Colombia. Method: The research was undertaken in two stages; in the first one, the citrus and mango production chain was characterized by collecting primary information, identifying raw materials and inputs used, as well as waste generated by each operation; in the second, an environmental diagnosis was made according to the critical activities of the production process. Results: Aspects related to production practices were identified in the citrus and mango production system of a Viotá association, with a cleaner production approach (cp). Conclusions: The research showed that the greatest environmental problems are associated with inadequate practices in the use of agrochemicals in the stages of fertilization, pest and disease control, as well as the inadequate disposal of inert waste.